Remote Monitoring and Holistic Care of Home-Isolated COVID-19 Positive Healthcare Workers Through Digital Technology During the Omicron (B1.1.529) Wave: A Prospective Cohort Study From India - Jain, Siddharth; Agarwal, Amit; Bhardwaj, Anupriya; Lakshmi, PVM; Singh, Manvi; Chauhan, Anil; Singh, Meenu (Frontiers in Public Health, 2022)
Background Remote monitoring through digital technology offers a promising solution for the diverse medical, psychological and social issues that plague patients with COVID-19 under home-isolation, but remain neglected due to a lack of streamlined medical services for these patients. Methods This prospective cohort study determined the feasibility of remote telemonitoring of healthcare workers with mild COVID-19 under home isolation during the Omicron (B1.1.529) wave and characterized their clinico-demographic profile. A holistic monitoring model comprising of mandatory phone calls at the beginning and end of isolation, assisted by home oximetry, predesigned google forms, and opt-in software-based (eSanjeevani OPD) teleconsultation was employed. Factors associated with development of symptomatic disease were also determined. Results Out of 100 COVID-19 positive healthcare workers under home-isolation, data for 94 participants was available [median age 27(20–52) years, 56(60%) females]. 93(99%) patients were previously vaccinated for COVID-19 (median time from last dose = 248 days); 34(36%) had a past history of COVID-19. Fever (67%), myalgia (69%), sore throat/dry cough (70%), and running nose (45%) were the most common symptoms. No patient progressed to moderate-severe disease or required care escalation during the remote monitoring period. Most participants reported several additional psychosocial concerns which were adequately addressed. Symptomatic patients had higher BMI (24.1 vs. 21.8kg/m2, p = 0.01) compared to asymptomatic patients. Age, past infection with COVID-19, and time since last vaccine dose were not different between symptomatic and asymptomatic patients. Conclusion COVID-19 patients under home isolation have multi-faceted medical and psychosocial issues which can be holistically managed remotely through digital technology.